Morphology of Hepatocytes in Methotrexate Induced Hepatotoxicity and Evaluate the Preventive Role of Antioxidant Agents in Rats: A Comparative Study (Medical Forum Monthly, 2022)
Objective: Compare the oxidative role of β-carotene (BC) and Resveratrol (RSV) in Methotrexate (MTX) induced liver toxicity based on histopathology.Study Design: A comparative studyPlace and Duration of Study: This study was conducted at the Pharmacology, Al-Tibri Medical College, Isra University Karachi Campus from January 2021 for a period of October 2021.Materials and Methods: 48 healthy Wistar albino rats were included in the study and divided into 6 groups each consisting of 8 subjects, Group I(Control group) was given Normal Saline, Group II was given BC, Group III was given RSV, Group IV MTX, Group V BC+MTX, Group VI RSV+MTX for a period of 24 days. On the 25th day, subjects were euthanized and the liver organ was extracted and sectioned to be studied under a light microscope with H&E staining being performed. For glycogen study, staining was carried out using PAS and for collagen fibers it was carried out using Trichome staining.Results: Normal Morphology, glycogen content, and deposition around the central vein was shown in Group I, II, and III. In Group IV central architecture was lost, congestion was seen around central vein, glycogen content was depleted, and deposition in collagen was present. In the both intervention Group V and VI, hepatic lobular architecture and hepatocytes were normal, uneven distribution of glycogen along with restoration was present, and no collagen was present.Conclusion: Beta-carotene and Resveratrol showed hepatoprotective effects in methotrexate induced hepatotoxicity in rats.